  Question: If -4 is a zero Of the polynomial x^2 - x - (2k+2) then k= Sanjeev J. from Delhi
• Like
We put value of given polynomial = 0 and value of x = -4. After solving equation we'll get value of k=9 S.Chandra from Kolkata
• Like

ATP, (-4)^2 - (-4) - 2(k+1) = 0

=>   16 + 4 = 2(k+1)      => 2(k+1) = 20    => k+1 = 10

=> k = 9     ... Ans.

N
Nikunj D. from Delhi
• Like

H
Himanki S. from Chandigarh
• Like

In this problem the zero of the polynomial is given = -4, which means if we substitute -4 in place of x in the equaltion then the equation must equate to 0

P(-4) = 0

P : x^2 - x - (2k+2)

As per the -4 being zero of polynomial Put x = -4 in above equation

(-4)^2 - (-4) -2k -2 = 0

16+4 -2k -2 =0

18-2K =0

k = -18/ -2

k = 9

M
Monika from Chennai
• Like

Given:

They have given ploynomial equation with zero polynomial

p(-4)=0,

substitute this p(-4)=0 in given eqation, then simplify, find K value.

k=9.  Ujjal H. from Kolkata
• Like
We know that if 'a' is a zero of polynomial p(X), then p(a)=0. Here -4 is the zero of the polynomial p(X)=x^2-x-(2k+2).So,p(-4)=0 ,=>(-4)^2-(-4)-(2k+2)=0,=>16+4=2k+2 ,=>k+1=10,=>k=9.
R
• Like
K = 9

### Post Answer and Earn Credit Points

Get 5 credit points for each correct answer. The best one gets 25 in all.

Similar Questions
Topic Cloud

## Need a Tutor or Coaching Class?

Post an enquiry and get instant responses from qualified and experienced tutors.

Post Requirement

Drop Us a Query